Biochemical markers and neuropsychological functioning in distal urea cycle disorders - Waisbren, Susan E.; Burgard, Peter (Journal of inherited metabolic disease, 2018)
Urea cycle disorders often present as devastating metabolic conditions, resulting in high mortality and significant neuropsychological damage, despite treatment. The Urea Cycle Disorders Longitudinal Study is a natural history study that collects data from regular clinical follow-up and neuropsychological testing. This report examines links between biochemical markers (ammonia, glutamine, arginine, citrulline) and primary neuropsychological endpoints in three distal disorders, argininosuccinic acid synthetase deficiency (ASD or citrullinemia type I), argininosuccinic acid lyase deficiency (ASA or ALD), and arginase deficiency (ARGD). Laboratory results and test scores from neuropsychological evaluations were assessed in 145 study participants, ages 3 years and older, with ASD (n = 64), ASA (n = 65) and ARGD (n = 16). Mean full scale IQ was below the population mean of 100 ± 15 for all groups: (ASD = 79 ± 24; ASA = 71 ± 21; ARGD = 65 ± 19). The greatest deficits were noted in visual performance and motor skills for all groups. While ammonia levels remain prominent as prognostic biomarkers, other biomarkers may be equally valuable as correlates of neuropsychological functioning. Cumulative exposure to the biomarkers included in the study proved to be highly sensitive indicators of neuropsychological outcomes, even when below the cut-off levels generally considered toxic. Blood levels of biomarkers obtained on the day of neuropsychological evaluations were not correlated with measures of functioning for any disorder in any domain. The importance of cumulative exposure supports early identification and confirms the need for well-controlled management of all biochemical abnormalities (and not just ammonia) that occur in urea cycle disorders.
Gesehen am 23.04.2019